(untitled) (Bangladesh Journal of Otorhinolaryngology, 2019)
Background: Otosclerosis is a disease of the otic capsule that is characterized by resorption and redeposition of bony tissue. Stapes surgery has established its position as the primary treament of conductive hearing loss in otosclerosis. It is anticipated that the hearing level of approximately 90% of patients should improve after surgery. Objective: To evaluate the hearing status of an otosclerotic patient and compare their preoperative and postoperative hearing status. Methods: In this prospective study, 34 patients with otosclerosis from head-Neck Surgery department of Sir Salimullah Medical College & Mitford Hospital, Bangladesh ENT Hospital, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka. Period from January 2008 to December 2008. The patients were examined and hearing assessment after admission into the hospital pre-operatively and in the post-operative period. Results: In this study most of the cases were age group 21-30 years (50%), male (64-71%), middle socio economic condition (67-71%), rural (58-82%), primary educated (35-29%). It was observed that most common symptom was progressive deafness; duration of hearing loss was 2-5 years, pre-operative conductive type of hearing loss (50-55 dB). It was also observed that after surgery, hearing status were improved in 82.35% cases, the most of the patients were within 21-30 years age group. Conclusion: Stapedotomy obtaining closure of the air-bone gap to within 10dB of the preoperative bone conduction level in 90% of their patients. So, it is supperior to other procedures Bangladesh J of Otorhinolaryngology; October 2018; 24(2): 137-142